Periungual Pyogenic Granuloma in Multiple Nails due to Isotretinoin - Ahluwalia, Daisy; Bansal, Shikha; Prathibha, Kuchana; Lachyan, Abhishek (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Isotretinoin, a first-generation nonaromatic retinoid approved in 1973 for severe nodulocystic acne treatment in the United States, has historically been associated with mucocutaneous adverse events. Case: The case involves a 22-year-old male with chronic plaque psoriasis who, after eight weeks of isotretinoin use, experienced swelling, pain, and bleeding in the periungual area of multiple fingers. Dermoscopic examination and follow-up assessments, including images, demonstrate the progression and eventual complete resolution of the periungual pyogenic granuloma following discontinuation of isotretinoin and topical application of fusidic acid and betamethasone combination. Discussion: The discussion delves into potential mechanisms linking isotretinoin to increased skin fragility and granulation tissue development, drawing on insights from experts like Baran and Piraccini. Additionally, we explore the role of angiogenic factors, particularly vascular endothelial growth factor (VEGF), in the context of psoriasis and its potential contribution to the development of pyogenic granuloma, with the aim of providing a comprehensive understanding of the underlying processes leading to this unique adverse event. Conclusion: In conclusion, this case report underscores the importance of recognizing and promptly addressing rare adverse events associated with medication errors. The successful resolution of the periungual pyogenic granuloma highlights the significance of timely intervention and appropriate management strategies in mitigating adverse outcomes.